Implizite Ekklesiologie im Galaterbrief - WOLTER, Michael (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
This article tries to show that Paul’s letter to the Galatians is guided by an implicit ecclesiological concept, the contours of which are clearly recognizable.